An exploratory study on the feasibility of adopting self-service fuel stations in Johannesburg: motorists' perspective - Uta, Lloyd Kudzanai (My University, 2015)
The South African petroleum industry is well-known to be a significant contributor to the country’s GDP. The industry is also known to employ close to 60000 employees in South Africa making it one of the most essential industries that is helping to uplift the country’s economy. However, like most industries in the country, the petroleum industry is not immune to strikes and go-slows which have increasingly become more pronounced over the years. This situation has consequently caused a number of problems for service stations as most service stations do not have complete control of the environment that they operate in, making it difficult for these fuel service stations to meet set targets and be able to ensure that greater profit margins are realised over time. This research sought to determine motorists’ perspectives on the adoption of self-service fuel stations in Johannesburg. The research focused on the adoption of these self-service fuel stations by assessing the general attitudes and perceptions of motorists on the innovation and findings have revealed that motorists generally accept the adoption of such an innovation provided that they understand and benefit from the functionality of adopting such innovations should they be introduced. The research was primarily a quantitative study and a five point likert scale questionnaire was distributed to potential respondents who were Johannesburg motorists above the age of 18 based on the motor-vehicle type they used. Results from the study revealed that motorists are more likely to consider adoption of Self-Service Fuel Stations provided they perceive such facilities to be useful and enhance their service experience at service-stations. Another interesting finding was that security and safety were a concern for most motorists who felt the variable will go a long way in influencing their decisions and attitude to consider adopting these facilities should they be introduced within the South African market. Marketers should therefore ensure that they consider the functionality and potential benefits that Self-Service Fuel Stations may have to Johannesburg motorists as this may go a long way in ensuring their wide adoption within the city should they be introduced.
Thesis (M. Com.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2015
Keywords: Self-service fuel stations; Perceived ease of use